2011
DOI: 10.1016/j.ajpath.2011.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Tubular Deficiency of von Hippel-Lindau Attenuates Renal Disease Progression in Anti-GBM Glomerulonephritis

Abstract: In many kidney diseases, the original insult primarily involves the glomerulus and may then pass onto the tubulointerstitium. Several hypotheses link glomerular disease to tubular injury; perhaps the foremost hypothesis involves chronic tubular hypoxia. The reported effects of hypoxia and consecutive stabilization of hypoxia-inducible factors (HIFs), however, are controversial. Hypoxia induces interstitial fibrosis but also has beneficial effects on renal disease progression when HIF is activated pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
4
17
0
Order By: Relevance
“…Additionally, work by Song et al demonstrated protective influences of pharmacological HIF induction in the kidney using DMOG, a known HIF stabilizer (51). Likewise, constitutive activation of HIF dampens glomerulonephritis progression, providing further evidence for beneficial influences of HIF for renal injury (52). Our results extend these findings to a murine model of septic renal injury, emphasizing the importance of renal HIF stabilization during kidney injury and hinting at potential beneficial influences of MLN4924 in various nephropathies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, work by Song et al demonstrated protective influences of pharmacological HIF induction in the kidney using DMOG, a known HIF stabilizer (51). Likewise, constitutive activation of HIF dampens glomerulonephritis progression, providing further evidence for beneficial influences of HIF for renal injury (52). Our results extend these findings to a murine model of septic renal injury, emphasizing the importance of renal HIF stabilization during kidney injury and hinting at potential beneficial influences of MLN4924 in various nephropathies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, knocking out pVHL in the thick ascending limb, which causes local HIF accumulation, significantly attenuated proximal tubular injury following ischemia-reperfusion by enhancing the glycolytic enzymes and lactate metabolism [39]. The conditional knockout of pVHL in tubular cells attenuated tubulointerstitial injury in anti-glomerular basement membrane glomerulonephritis by enhancing the angiogenic factors and growth factors [40]. The activation of HIF in infiltrating myeloid cells by VHL-conditional knockout suppressed inflammation in the UUO model [38].…”
Section: Role Of Hypoxia-inducible Factors In Chronic Kidney Diseasementioning
confidence: 98%
“…Myofibroblast formation in kidney may depend on environmental cues, such as the presence of inflammatory molecules. 5 Alternatively, normalization of hematocrit in Vegfa tub mice could be envisioned to promote enhanced stabilization of hypoxia-inducible factors and augment the expression of their target genes, such as plateletderived growth factor, 24 which has previously been shown to be important for myofibroblast formation. 25 Whether the myofibroblasts are derived from REPs or other cell types remains to be determined.…”
Section: Discussionmentioning
confidence: 99%